Engaging social justice critical studies of 21st century social transformation - Fasenfest, David (Chicago, Ill. Haymarket Books, 2011)
"The global economic collapse of 2008 has brought into sharp relief the penetration of global capitalism and its impact on working people both in the industrial core and in developing nations. In response, social movements challenging the World Trade Organization and annual gathering of progressive groups and NGOs at the World Social Forums have embarked on the goal of creating an alternative to the neo-liberal policies that have immiserated generations. The articles in this book address the need for a progressive pedagogy, highlight the organizational forms of resistance to capitalism, and explore new forms of struggles against capitalist practices by people throughout the world."--Book jacket.
Towards a progressive future / David Fasenfest -- Teaching toward praxis and political engagement / Melanie E. L. Bush and Deborah L. Little -- Another world is possible : mobilizing for global justice / Lauren Langman -- SMOs, cyberactivism, and entertainment as politics : how MoveOn is expanding public discourse and political struggle / Victoria Carty -- Extending theories of NGOs : committed HIV/AIDS activists and neoliberal reforms in Ukraine / Arseniy Gutnik -- Stability and change in the contours of alliances among movements in the social forum process / Christopher Chase-Dunn and Matheu Kaneshiro -- The globalization movement and world social forum : from protest to politics / Heather Gautney -- The technocratization of protest : transnational advocacy organizations and the WTO / Kristen Hopewell -- Emerging emancipatory processes in Latin America / Ximena de la Barra and R.A. Dello Buono -- Migration and asymmetrical integration in Latin America / Vâictor M. Figueroa Sepâulveda -- What is the potential of Latin America's "third left"? / Marie Kennedy, Fernando Leiva and Chris Tilly -- Resurrected enterprises and social mobilization in Argentina / Laura Collin Harguindeguy -- Community organizing, rebellion, and the progressive state : neighborhood councils in El Alto, Bolivia / Emily P. Achtenberg -- The Zapatistas' other politics : the subjects of autonomy / Margaret Cerullo.
"First published in 2009 by Brill"--T.p. verso.
Includes bibliographical references (p. [307]-331) and indexes.
Keywords: Social justice; Social change; Capitalism